Inspeksi Hasil Sambungan Pengelasan SMAW pada Pembuatan Frame Acid Skid dengan Metode Liquid Penetrant Testing - Parlin Jhony Haposan Siagian; Nurul Laili Arifin; Nurul Ulfah; Hanifah Widiastuti (Jurnal Teknologi dan Riset Terapan (JATRA), 2022)
In this era of globalisation, many industrial companies have been built, especially in the chemical field. Chemical industry companies need a tank to store chemicals production result with a framework design that is nice and strong and can be moved easily. The material used is the type of carbon steel (S275JR) using the SMAW welding process at 6G welding position with intermediate currents in 59 A-134A. The type of joint for the frame is butt-joint, fillet joint and lap joint. In order to guarantee the quality of the welding results, the material will be tested in Non-Destructive Testing with the Inspection method using liquid penetrant, the penetrant method is solvent removable with visible sensitivity at a light level intensity of 1000 lux. The welding results are determined based on acceptance criteria in AWS with ASME as a critical reference. If there no defects or discontinuities like liniear and rounded were found in section of pad eye and base frame, then all welding results will be accepted.